Addressing desertification in Algeria: Etiologies, National Policies, and Accomplishments - Benhizia, Ramzi; Saidi , Feyrouz Ahlam; Aib, Haithem; Szabó, György (Acta Geographica Debrecina Landscape & Environment series, 2026)
Desertification, affects 36.62% of non-desert land in Algeria, stands as a critical environmental challenge demanding thorough analysis and strategic intervention. This study offered a nuanced exploration of the multifaceted dynamics of desertification, scrutinizing its varied causes, ecological repercussions, and governmental countermeasures. Drawing on extensive research, the article synthesizes insights from previously overlooked factors such as colonialism, wildfires, socio-economic shifts, and the evolving climate landscape. Since 1962, Algeria has committed to mitigate desertification through strategic programs into national development plans, intricately woven into the fabric of national development plans. Noteworthy among these initiatives is the vegetation barrier project, conceived to erect a formidable vegetation barrier against the relentless advance of encroaching deserts. The legal and institutional frameworks, coupled with meticulous planning under the National Spatial Development Plan (SNAT 2025), underscore Algeria’s proactive stance. Despite commendable achievements in afforestation, watershed protection, and socio-economic development, persistent challenges underscore the need for continued collaboration, adaptive strategies, and an unwavering commitment to mitigating the profound impacts of desertification on Algeria’s diverse ecosystems and communities.